Systematic review of challenges and prospective recommendations of medically assisted reproductive technology in developing countries - Mesfin, Melese Dereje; Galgallo, Dahabo Adi; Atmaca, Leman; Kovács, Kálmán András; Várnagy, Ákos; Prémusz, Viktória (Frontiers in Reproductive Health, 2025)
IntroductionInfertility is a global public health issue which affects significant portion of adult population. In developing nations, infertility has long been disregarded as a reproductive health problem. Despite being available for almost for five decades, most people in resource-poor nations still face challenges to access assisted reproductive technology. We conducted this systematic review to explore the reasons behind such gaps and solutions outlined to address them.MethodsAfter a study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO), we conducted a comprehensive search using predefined keywords and medical subject headings across major electronic databases: - Ovid MEDLINE, PubMed, Web of Science, and Google Scholar.Results and DiscussionThe database search resulted in total of 3097 citations; after removal of 2256 duplicates, 765 citations were selected for title and abstract review. A full text review was conducted on the 137 articles 43 studies were included in the final analysis. The majorly cited challenge was the high costs associated with treatment, followed by accessibility and infrastructural obstacles, psychosocial and cultural barriers including the unacceptance of a baby born from assisted reproduction. Absence of supportive policies coupled with religious factors worsen the problem. Governmental, non-governmental, and international organizations should collaborate to address affordability and accessibility issues and to resolve socio-cultural and religious challenges through the inclusion of infertility treatment in the existing health system, revisiting the financial mechanisms, and creating supportive policies in partnership with community and religious leaders.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025632094, PROSPERO CRD42025632094.